2011
DOI: 10.1002/pits.20574
|View full text |Cite
|
Sign up to set email alerts
|

Ethically challenging situations reported by school psychologists: Implications for training

Abstract: Practitioner-members of the National Association of School Psychologists (N = 208) completed questionnaires regarding their ethics training, preparedness, the types of ethical transgressions and dilemmas encountered in the previous year, and the strategies used to solve problems. Respondents who received multilevel training in ethics (ethics coursework, ethics instruction in multiple classes, ethics addressed in practicum/internship) perceived themselves to be better prepared to tackle difficult challenges and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 23 publications
2
24
0
1
Order By: Relevance
“…Future studies could investigate these phenomena also in terms of qualitative content. Some research has already shown what kinds of ethical dilemmas are typically encountered in school psychologists’ work (see, e.g., Dailor & Jacob, ; Jacob‐Timm, ), but a more detailed understanding of what causes stress when facing these dilemmas, and of the actual dimensions of rumination and worry (e.g., whether thoughts are related to trying to solve the dilemma or more to affective rumination) could be the aims of future studies. Finally, the role of personal features regarding the strain experiences should be addressed in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Future studies could investigate these phenomena also in terms of qualitative content. Some research has already shown what kinds of ethical dilemmas are typically encountered in school psychologists’ work (see, e.g., Dailor & Jacob, ; Jacob‐Timm, ), but a more detailed understanding of what causes stress when facing these dilemmas, and of the actual dimensions of rumination and worry (e.g., whether thoughts are related to trying to solve the dilemma or more to affective rumination) could be the aims of future studies. Finally, the role of personal features regarding the strain experiences should be addressed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…There are still very few studies about ethical decision making and its consequences among psychologists working in schools. Dailor and Jacob () are among the most recent researchers to have investigated the ethically challenging situations that school psychologists experience in a study that was based on retrospective self‐evaluations. Using multiple‐choice survey questions they found that almost three quarters of the respondents had encountered at least one of eight types of ethical dilemma within the previous year.…”
Section: Ethical Strain In School Psychologists’ Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Doctoral programs in clinical, counseling, and school psychology often fail to meet child maltreatment training standards, even when these issues are addressed in their curricula (Champion, Shipman, Bonner, Hensley, & Howe, 2003). On a recent questionnaire completed by over 200 practicing school psychologists, the most commonly reported ethical dilemma faced in the past year was whether or not to contact CPS when child abuse was suspected, despite the fact that 90% of respondents had at least some formal ethics training (Dailor & Jacob, 2011).…”
Section: The Role Of the School Psychologistmentioning
confidence: 99%
“…To demonstrate their commitment to ethics, and to promote high standards of ethical conduct among its members, some professional associations have developed codes of ethics and conduct to support those working in school settings (e.g., International School Psychology Association, 2011;NASP, 2010). In parallel, several studies have explored ethical issues in professional psychology with implications for school psychology (Dailor & Jacob, 2011;Jacob-Timm, 1999;Pettifor & Sawchuk, 2006;Pope & Vetter, 1992). Most of these studies relied on United States samples and used the critical incident technique or structured inquiries.…”
mentioning
confidence: 99%